Cholesteric and blue-phase liquid photonic crystals for nonlinear optics and ultrafast laser pulse modulations. Issue 1 (2nd January 2018) - Khoo, Iam Choon
ABSTRACT: We present a comprehensive review of nonlinear optics and photonics of two ordered phases of liquid crystals, namely, Cholesteric and Blue-phase liquid crystals that exhibit 1- and 3-D photonic crystalline properties. We delve into the ultrafast individual molecular electronic nonlinearity as well as crystalline non-electronic nonlinearities arising from laser induced electrostriction, thermal-, density- and order parameter changes, director axis reorientation and lattice distortion. Emphasis is placed on exploring the unique advantages associated with their liquid crystalline and photonic crystal properties. Exemplary feasibilities demonstration of all-optical passive eye/sensor protection, femtoseconds and picoseconds pulse modulations, lasing actions, aberration-free optical phase conjugation and all-optical image processing and holographic recording are presented along with a critical review and comparison with their nematic counterparts and other electro-optical or nonlinear optical materials.